Stereotactic radiosurgery in alveolar soft part sarcoma brain metastases: Case series and literature review. (November 2021) - Lim, Jia Xu; Karlsson, Bengt; Pang, Angela; Vellayappan, Balamurugan A.; Nga, Vincent
Highlights: ASPS has the highest incidence of brain metastasis amongst sarcomas. High prescription doses necessary to achieve local tumour control. Retreatment of lesions with SRS local recurrence is effective. SRS can be used for ASPS brain metastases that are not surgically accessible. Abstract: Alveolar soft part sarcoma (ASPS) has the highest incidence of brain metastasis amongst sarcomas. There is a paucity of literature published focusing on radiation therapy for this condition. This is a single centre retrospective review of the treatment of three patients with 12 ASPS brain metastasis using single dose stereotactic radiosurgery (SRS). Five lesions were treated with low (<25 Gy) and seven with high (≥25 Gy) dose. Four lesions had a volume of >1.5 cm 3 and were defined as large, while seven had a volume of ≤0.5 cm 3 and were defined as small. The local tumor control as well as the clinical complication rates were studied. There was a statistically significant relation between treatment dose and tumor control rate. All large tumors treated with low dose recurred and required surgical removal within two months following SRS, while the large lesion treated with high dose recurred after 11 months. Five of the six small tumors treated with high doses were controlled, while the sixth required retreatment and was stable thereafter. No patient suffered from undue symptomatic radiation effects. The success rate following SRS for small ASPS metastases treated with high doses seems to be sufficient to justify the treatment. The short time for large tumor to recur, significant increase in tumor size requiring surgical removal of the tumors, makes low dose SRS unattractive. Based on this limited patient population, it seems that high dose SRS should be used for all ASPS brain metastases except for large tumors deemed surgically accessible.